Plasma protein thiols: an early marker of oxidative stress in asthma and chronic obstructive pulmonary disease. (8th January 2016) - Zinellu, Angelo; Fois, Alessandro Giuseppe; Sotgia, Salvatore; Zinellu, Elisabetta; Bifulco, Fabiana; Pintus, Gianfranco; Mangoni, Arduino A.; Carru, Ciriaco; Pirina, Pietro
Abstract: Chronic obstructive pulmonary disease (COPD) and asthma are both characterized by heterogeneous chronic airway inflammation and obstruction as well as oxidative stress (OS). However, it is unknown whether OS occurs in early disease and how to best assess its presence. Plasma OS markers (TBARS, PSH, taurine, GSH, ergothioneine and paraoxonase 1 activity) and lung function tests were measured in patients with mild stable asthma ( n = 24) and mild stable COPD ( n = 29) and in age‐ and sex‐matched controls. Forced expiratory volume in 1 s (FEV1 ) was associated with age both in patients and control groups. By contrast, FEV1 was positively correlated with PSH only in COPD (ρ = 0·49, P = 0·007). In multiple logistic regression analysis, lower PSH was the only OS marker independently associated with increased odds of both asthma (OR = 0·32, 95% CI 0·13–0·78, P = 0·01) and COPD (OR = 0·50, 95% CI 0·26–0·95, P = 0·03). These findings suggest that proteins ‐SH are a sensitive OS marker in early COPD and asthma.